2010
DOI: 10.3109/09553002.2010.501838
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mobile phone use on brain tissue from the rat and a possible protective role of vitamin C – a preliminary study

Abstract: Our results suggest that vitamin C may play a protective role against detrimental effects of mobile phone radiation in brain tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…It is well accepted that vitamin C is the potent antioxidant (39) in biological fluids for protection against degenerative processes of oxidative stress in the brain and other tissues (3,23,24,40).…”
Section: Discussionmentioning
confidence: 99%
“…It is well accepted that vitamin C is the potent antioxidant (39) in biological fluids for protection against degenerative processes of oxidative stress in the brain and other tissues (3,23,24,40).…”
Section: Discussionmentioning
confidence: 99%
“…Results of the current study showed that vitamin C significantly reduced pituitary oxidative stress and apoptosis as reflected by decreased levels of MDA, 8-OHdG, and caspase-3 and increased levels of SOD compared to rats exposed to mobile phone EMR. Vitamin C is a powerful natural antioxidant that protects cells from the damaging effect of ROS by scavenging free radicals [27]. In addition, previous reports showed that vitamin C can prevent EMRinduced oxidative stress damage and apoptosis of endometrium and brain cells [27] [28].…”
Section: Resultsmentioning
confidence: 99%
“…Based on other similar studies, it is also advised to consume a balanced, nutritious diet that provides adequate antioxidants, as antioxidants have been proved to be protective against damage by electromagnetic radiation-induced oxidative stress. [22,23] …”
Section: Discussionmentioning
confidence: 99%